Sicilian ghost story [videorecording (DVD)] - Grassadonia, Fabio; Piazza, Antonio; Jedlikowska, Julia; Fernandez, Gaetano; Musallari, Corinne (Strand Releasing Home Video, 2017)
It is the haunting, hypnotic tale of a mysterious disappearance set in a little Sicilian village on the edge of a forest. Thirteen-year-old Luna, always dreaming, has a crush on her handsome classmate Giuseppe; they begin a tentative romance. But one day Giuseppe fails to show up at school. As the days pass with no sign of him, Luna tries to raise concern with family and friends.